RECRUITMENT AND EMPLOYEE SELECTION STRATEGIES IN IMPROVING THE QUALITY OF HUMAN RESOURCES IN BANDUNG CITY - Ade Mubarok (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2021)
Human resources are important assets that determine organizational success and competitiveness. This study aims to analyze recruitment and employee selection strategies in improving the quality of human resources in Bandung City. The research used a qualitative descriptive method involving human resource managers, recruitment staff, and employees from several public and private organizations in Bandung City. Data were collected through interviews, observations, and documentation analysis, then analyzed using descriptive qualitative techniques. The results showed that competency-based recruitment and structured employee selection systems significantly contribute to improving human resource quality. Organizations that implemented transparent recruitment procedures, digital recruitment platforms, competency assessments, and structured interviews were more successful in attracting qualified employees and improving organizational performance. In contrast, organizations using conventional recruitment methods faced challenges such as recruitment inefficiency, mismatches between employee competencies and job requirements, and higher employee turnover rates. The study also identified several obstacles in recruitment implementation, including limited technological infrastructure, inadequate human resource management capabilities, and the persistence of non-merit-based recruitment practices. Therefore, organizations are encouraged to strengthen competency-based recruitment systems, improve transparency in selection procedures, and optimize the use of digital technology in recruitment activities. In conclusion, effective recruitment and employee selection strategies play a significant role in enhancing the quality of human resources in Bandung City. The implementation of fair, transparent, and technology-supported recruitment systems is expected to improve organizational productivity, employee performance, and long-term competitiveness.